(untitled) (Conferencea, 2022)
Аny culture is not stable; it is in constant motion and change, in harmony with the surrounding environment. Language is such that it collects, stores, transmits data from generation to generation. Linguo-culturology is one of the most dynamically developing spheres of modern linguistics.